Computability at zero temperature*Burr was partially supported by the National Science Foundation Grants CCF-1527193 and DMS-1913119. Wolf was partially supported by Grants from the PSC-CUNY (TRADB-49-253 to Christian Wolf) and the Simons Foundation (#637594 to Christian Wolf). (6th October 2020) - Burr, Michael; Wolf, Christian
Abstract: We investigate the computability of thermodynamic invariants at zero temperature for one-dimensional subshifts of finite type. In particular, we prove that the residual entropy (i.e., the joint ground state entropy) is an upper semi-computable function on the space of continuous potentials, but it is not computable. Next, we consider locally constant potentials for which the zero-temperature measure is known to exist. We characterize the computability of the zero-temperature measure and its entropy for potentials that are constant on cylinders of a given length k . In particular, we show the existence of an open and dense set of locally constant potentials for which the zero-temperature measure can be computationally identified as an elementary periodic point measure. Finally, we show that our methods do not generalize to treat the case when k is not given.